A Retrospective Study on 1587 Exotic Pets Presented to The Small Animal Veterinary Hospital, University of Tehran - Tamimi, Naqa S. M; T., Bahare; J, Shahram; R., Amir (The Iraqi Journal of Veterinary Medicine, 2020)
In recent decades, exotic pets are increasingly invited to homes with a wide range of variation in species and requirements that are more specialized. During a one-year period, 2408 exotic animals admitted to the Small Animal Veterinary Hospital, University of Tehran were assessed. Rabbits, hamsters, squirrels, turtles/tortoises, guinea pigs, lizards, hedgehogs, reindeer, monkeys, and snakes were referred, respectively. Owner referral cause and their gender in addition to the disease diagnosis were analyzed. While no statistical significance (P>0.05) was observed in the total number of men and women presenting these animals, gender-based preferences were spotted for owning specific types of animal species in this study (P<0.05). Furthermore, analysis showed that snakes and rabbits were more commonly (P<0.05) presented for checkup; while chelonians, lizards, hedgehogs, and monkeys were more presented with health problems (P<0.05). Other animals’ results did not show statistically significant difference for admission reasons (P>0.05). The health record assessment included 1587 animals with complete health files. The most common diseases diagnosed in most of these animals were metabolic bone disease/musculoskeletal problems and dental problems. In addition, eye problems in chelonians and urinary problems in hedgehogs were the most common diagnosis of those species. In conclusion, since the most common health problems of most participating animals were associated with mismanagement and inappropriate diet, it is highly recommended that owners be thoroughly educated by veterinarians to reduce the possibility of such conditions in exotic captive animals.